Hepatitis B virus strains from Rwandan blood donors are genetically similar and form one clade within subgenotype A1. Issue 1 (December 2017) - Twagirumugabe, Theogene; Swaibu, Gatare; Walker, Timothy; Lindh, Magnus; Gahutu, Jean; Bergström, Tomas; Norder, Heléne
Abstract Background Rwanda is a central African country with about 12 million inhabitants. The 1994 genocide against the Tutsi destroyed much of the infrastructure, including the health system. Although this has improved significantly, many challenges remain to be addressed. In this study, the prevalence of serological markers of past and ongoing hepatitis B virus (HBV) infection and HBV vaccine related immunity was investigated in samples from blood donors from all regions of Rwanda. Methods The results from hepatitis B surface antigen (HBsAg) analyses of all (45, 061) blood donations collected countrywide in 2014 from 13, 637 first time and 31, 424 repeat blood donors were compiled. Samples from 581 HBsAg negative blood donors were selected for further analysis for antibodies against HBV, anti-HBs and anti-HBc. Additional 139 samples from HBsAg positive donors were analyzed for HBeAg/anti-HBe (132 samples) and for HBV DNA. The S-gene was amplified by PCR, products sequenced, and phylogenetic analysis was performed. Results HBsAg was found in 4.1% of first time donors with somewhat higher prevalence among those from the Central and Eastern regions than from other parts of the country. Indications of past infection was found in 21% of the HBsAg negative donors, 4.3% had only anti-HBs suggesting HBV vaccination. HBeAg was detected in 28 (21%), anti-HBe in 97 (73%), and both HBeAg and anti-HBe in 4 of 132 HBsAg positive donors. HBV DNA was found in 85 samples, and the complete S-gene was sequenced in 58 of those. Phylogenetic analysis of the sequences revealed that all HBV strains belonged to subgenotype A1, and formed one clade in the phylogenetic tree. In addition, 12 strains from first time donors had a unique 18 amino acid deletion in the N-terminal part of the pre-S2 region. Conclusion This study indicated that the prevalence of hepatitis B is intermediate in Rwanda and that the vaccination coverage is relatively low in young adults. All surveyed Rwandan blood donors were infected with similar subgenotype A1 strains, and a high frequency of those with anti-HBe had detectable HBV DNA. Several strains had in addition a unique pre-S2 deletion, the virulence of which needs to be further studied.